Performance Determinants - Amal Maulana, Ikhlasul; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to examine the influence of organizational culture and individual characteristics on the performance of employees of BPJS Ketenagakerjaan Aceh Raya Branch Office with work experience as a moderating variable. The type of research that researchers use is quantitative research. The population and sample in this research are all permanent employees at PT. BPJS Employment Banda Aceh Branch Office has 70 employees (saturated sample). Data analysis in this research uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.334 and a p value of 0.007. Individual Character has a positive and insignificant effect on Employee Performance with an original sample value of 0.382 and a p value of 0.069. Work Experience has a positive and insignificant effect with an original sample value of 0.258 and a p value of 0.147. Organizational culture has a positive and insignificant effect on employee performance and work experience is not able to moderate it with the original sample result being 0.079 and p value 0.671. Individual characteristics have a negative and insignificant effect and are moderated by work experience with an original sample value of -0.084 and a p value of 0.597.